The effect of infliximab, cyclosporine A and recombinant IL-10 on vitreous cytokine levels in experimental autoimmune uveitis - Demir, Tamer; Gödekmerdan, Ahmet; Balbaba, Mehmet; Türkçüoglu, Peykan; Ilhan, Fulya; Demir, Nesrin (Medknow Publications and Media Pvt. Ltd, 2006)
Background: To identify the effect of infliximab, cyclosporine A and recombinant IL-10 in experimental autoimmune uveitis. Materials and Methods: Sixty male rats were assigned to five groups of 12 each. All the groups (except the control group) were administered 30 ?g retinal-S antigen intraperitoneally. On the 14th day, after confirmation of uveitis with histopathological study, daily cyclosporine A injection was given in cyclosporine A treatment group and physiological serum in the uveitis-induced placebo treatment and control groups. In the infliximab treatment group, infliximab was administered on the 14th, 15th, 17th, 19th and 21st days. In the recombinant IL-10 treatment group, three doses of recombinant IL-10 were given four hours and a half hours before and eight hours after retinal-S antigen administration. On the 21st day of the study, all rats were sacrificed and vitreous cytokine levels (IL-1, IL-6, IL-8 and TNF-a) were studied with ELISA. Results: In the treatment groups, cytokine levels (IL-1, IL-6 and TNF-a) were significantly lower than the uveitis-induced placebo treatment group. Compared with the control group, there was no significant difference with respect to TNF-a and IL-8 in the infliximab treatment group; IL-8 in the cyclosporine A treatment group; IL-6 and IL-8 in the recombinant IL-10 treatment group. The drugs used did not significantly differ in respect to their effects on vitreous IL-6, IL-8 and TNF-a levels. Conclusion: Cyclosporine A, infliximab and recombinant IL-10 reduce the vitreous cytokines levels. Among these drugs, recombinant IL-10, which is still in its experimental phase, might be considered as a new therapeutic agent.
Keywords: Cyclosporine A; Experimental autoimmune uveitis; Infliximab; Recombinant IL-10